Lockdown, Work at Home as Impact Corona Viruses Sustainability of Warteg Traders in Cimahi - Drajat Sulistiyono (Journal of Sustainable Business Hub, 2020)
Abstract: Lockdown, working at home as a impact corona viruses of the sustainability of the warteg traders in Cimahi. The purpose of this research is to study and analyze the effects of lockdown and working at home caused by the corona virus that contributes to the survival of warteg traders in the city of Cimahi. The results of the study consider simultaneous test Y = 0.620 + 0.221 X1 + 0.498 X2 From the problems above where lockdown and work at home are very influential, we hope that the corona virus will be resolved soon and the Indonesian government will eliminate Lockdown and work at home, so that the survival of Warteg entrepreneurs in Cimahi City will be stable again.. Keyword: Lockdown, Work at Home, Sustainability of Warteg Traders